(untitled) (Development Service Industry Management, 2024)
The article defines the conceptual provisions of the formation of the enterprise’s financial support management system, which are designed to determine the basics of designing the functional directions of its activity and development. The basic methodological toolkit is highlighted (the method of extrapolation (consists in determining the financial and economic indicators of the enterprise on the basis of identifying their dynamics), the regulatory method (based on the use of basic norms and standards that must be followed in the enterprise management system), the method of mathematical modeling (consists in construction of financial models that simulate the course of real processes), the balance method (intended to coordinate the directions of the use of financial resources with the sources of their formation, linking all sections of financial plans with each other)) management of projects of financial support of the enterprise. It is emphasized that the toolkit for managing financial support projects of the enterprise should be focused on the regulation of organizational processes (development of internal documents that define responsible parties, document flow model), methodical (implementation of mechanisms that ensure the implementation of specific management actions), personnel (organization of the work of a set of services or employees , which carry out the development and implementation of projects), informational (creation of a database in terms of all necessary types of financial and auxiliary information), technical (implementation of a complex of technical means, software, other means of information processing), regulatory and legal (observance of a set of legislative acts, which regulate the process of managing financial resources) provision. Organizational changes, establishment of control, introduction of mechanisms of regulation of entrepreneurial activity are established as priority tools for managing projects of financial support of the enterprise.